Genomic signatures of divergent selection and speciation patterns in a 'natural experiment', the young parallel radiations of Nicaraguan crater lake cichlid fishes - Kautt, Andreas F.; Elmer, Kathryn R.; Meyer, Axel (My University, 2012)
Divergent selection is the main driving force in sympatric ecological speciation and may also play a strong role in divergence between allopatric populations. Characterizing the genome-wide impact of divergent selection often constitutes a first step in unravelling the genetic bases underlying adaptation and ecological speciation. The Midas cichlid fish (Amphilophus citrinellus) species complex in Nicaragua is a powerful system for studying evolutionary processes. Independent colonizations of isolated young crater lakes by Midas cichlid populations from the older and great lakes of Nicaragua resulted in the repeated evolution of adaptive radiations by intralacustrine sympatric speciation. In this study we performed genome scans on two repeated radiations of crater lake species and their great lake source populations (1030 polymorphic AFLPs, n ∼ 30 individuals per species). We detected regions under divergent selection (0.3% in the crater lake Xiloá flock and 1.7% in the older crater lake Apoyo radiation) that might be responsible for the sympatric diversifications. We find no evidence that the same genomic regions have been involved in the repeated evolution of parallel adaptations across crater lake flocks. However, there is some genetic parallelism apparent (seven out of 51 crater lake to great lake outlier loci are shared; 13.7%) that is associated with the allopatric divergence of both crater lake flocks. Interestingly, our results suggest that the number of outlier loci involved in sympatric and allopatric divergence increases over time. A phylogeny based on the AFLP data clearly supports the monophyly of both crater lake species flocks and indicates a parallel branching order with a primary split along the limnetic-benthic axis in both radiations.
Keywords: 570